Embroidering Myself into Otherness : an Auto-ethnographic Inquiry of Border-crossing - Scott, Joy Denise (Curtin University, 2013)
This auto-ethnographic inquiry explores the complexities and singularities of a western teacher immersed in the social reality of a Chinese university. Focusing on the specifics of my relationships with Chinese colleagues and students, I offer an alternative way of interpreting intercultural relations. Through these relationships I foreground inclusion, exclusion, contradiction and the complexity of everyday life, and ask: who is the Chinese other? Who is the foreigner? What can they teach each other?